Extracellular Vesicles as an Emerging Treatment Option for Intervertebral Disc Degeneration: Therapeutic Potential, Translational Pathways, and Regulatory Considerations. Issue 5 (23rd July 2021) - DiStefano, Tyler J.; Vaso, Keti; Danias, George; Chionuma, Henry N.; Weiser, Jennifer R.; Iatridis, James C.
Abstract: Emergent approaches in regenerative medicine look toward the use of extracellular vesicles (EVs) as a next‐generation treatment strategy for intervertebral disc (IVD) degeneration (IVDD) because of their ability to attenuate chronic inflammation, reduce apoptosis, and stimulate proliferation in a number of tissue systems. Yet, there are no Food and Drug Administration (FDA)‐approved EV therapeutics in the market with an indication for IVDD, which motivates this article to review the current state of the field and provide an IVD‐specific framework to assess its efficacy. In this systematic review, 29 preclinical studies that investigate EVs in relation to the IVD are identified, and additionally, the regulatory approval process is reviewed in an effort to accelerate emerging EV‐based therapeutics toward FDA submission and timeline‐to‐market. The majority of studies focus on nucleus pulposus responses to EV treatment, where the main findings show that stem cell‐derived EVs can decelerate the progression of IVDD on the molecular, cellular, and organ level. The findings also highlight the importance of the EV parent cell's pathophysiological and differentiation state, which affects downstream treatment responses and therapeutic outcomes. This systematic review substantiates the use of EVs as a promising cell‐free strategy to treat IVDD and enhance endogenous repair. Abstract : Extracellular vesicles are an emerging cell‐free treatment strategy for intervertebral disc degeneration with demonstrated therapeutic potential to promote endogenous repair. This systematic review identifies all preclinical studies to‐date that investigate the use of stem cell‐ or primary cell‐derived extracellular vesicles to treat models of intervertebral disc degeneration, aggregates their outcomes, and highlights future directions to advance this next‐generation treatment strategy.